AKTIVITAS FISIK DAN KESEHATAN MENTAL SISWA SMA PADA ADAPTASI KEHIDUPAN BARU - Delvya Intan Kusumawardhani; Indra Himawan Susanto; Pudjijuniarto Pudjijuniarto; Yetty Septiani Mustar (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2021)
Physical activity and mental health are very important in the community, especially during the adaptation to the new normal. This study figures for the physical activity and mental health of students of SMA Negeri 1 Karas Magetan during the new normal adaptation. This research is a descriptive quantitative study using a survey as data collection, the instrument used for data collection is using GPAQ to determine physical activity and GHQ-12 to determine mental health. The subjects were students of SMA Negeri 1 Karas Magetan with a sample of 300 students. Sample selection of examples using cluster random sampling. Data analysis using descriptive analysis. From the GPAQ analysis, there were 3 categories of physical activity. Male physical activity was dominated by moderate activity as many as 37 students or 48%, high physical activity as many as 32 students or 42%, low activity as many as 8 students or 10%, while women's physical activity was dominated by categories of high and moderate physical activity were 89 students or 40%, low physical activity was 45 students or 20%. Students of SMA Negeri 1 Karas Magetan spent an average of 230.30 minutes (3.84 hours) of sedentary activities per day. From an analysis of GHQ-12 results, an average of 12.86 were able to enter the usual pressure, the average male student was 10.04 under low pressure, along with an average female student of 13.83 under more pressure than usual. The conclusion is that the level of physical activity of SMA Negeri 1 Karas Magetan students have met WHO recommendations regarding physical activity for health. The mental health of SMA Negeri 1 Karas Magetan students is still under the usual pressure category.